TransInformação Vol. 25, n. 1 (2013) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
TransInformação Vol. 25, n. 1 (2013)Link de acesso ao númerohttp://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/issue/view/273